Immune responses in multiple hosts to Nucleocapsid Protein (NP) of Crimean-Congo Hemorrhagic Fever Virus (CCHFV) - Karaaslan, Elif; Çetin, Nesibe Selma; Kalkan-Yazıcı, Merve; Hasanoğlu, Sevde; Karakeçili, Faruk; Özdarendeli, Aykut; Kalkan, Ahmet; Kılıç, Ali Osman; Doymaz, Mehmet Ziya (PLOS Neglected Tropical Diseases, 2021)
In 2019, the World Health Organization declared 3 billion to be at risk of developing Crimean Congo Hemorrhagic Fever (CCHF). The causative agent of this deadly infection is CCHFV. The data related to the biology and immunology of CCHFV are rather scarce. Due to its indispensable roles in the viral life cycle, NP becomes a logical target for detailed viral immunology studies. In this study, humoral immunity to NP was investigated in CCHF survivors, as well as in immunized mice and rabbits. Abundant antibody response against NP was demonstrated both during natural infection in humans and following experimental immunizations in mice and rabbits. Also, cellular immune responses to recombinant NP (rNP) was detected in multispecies. This study represents the most comprehensive investigation on NP as an inducer of both humoral and cellular immunity in multiple hosts and proves that rNP is an excellent candidate warranting further immunological studies specifically on vaccine investigations.